Penerapan Metode One-Time Pad Chiper untuk Mengamankan Data Karyawan pada PT. Transima Citra Indo Consultant - Sinaga, Salsa Carissa; Fithry Tahel (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2025)
PT. Transima Citra Indo Consultant, a company engaged in the field of tax consulting, requires a reliable data security system to maintain the confidentiality of sensitive information. One of the cryptographic methods that can be used is the One-Time Pad (OTP) method. One-Time Pad is an encryption algorithm with a very high level of security because it uses a unique key throughout the original message, thus ensuring that the encrypted message cannot be cracked as long as the key remains confidential. Therefore, this study will discuss the application of One-Time Pad in protecting employee data at PT. Transima Citra Indo Consultant as an effort to improve company data security. The results of this study are expected to provide significant benefits to PT. Transima Citra Indo Consultant in securing employee data, and also ensuring that only authorized parties can access it.